1919 Vt. Acts and Resolves 136, No.128, § 1. - (:unkn) unknown (My University, 1919)
It shall be unlawful to transport, carry or convey from one place in this state to another place in this state, any dynamite, gunpowder, or other explosive on any vessel or vehicle of any description operated by a common carrier, which vessel or vehicle is carrying passengers for hire[.]
Keywords: GUNPOWDER - TRANSPORTATION